Transport and Transportation Pathways of Hazardous Chemicals from Solid Waste Disposal - Van Hook, Robert I. (Environmental health perspectives, 1978)
To evaluate the impact of hazardous chemicals in solid wastes on man and other organisms, it is necessary to have information about amounts of chemical present, extent of exposure, and chemical toxicity. This paper addresses the question of organism exposure by considering the major physical and biological transport pathways and the physicochemical and biochemical transformations that may occur in sediments, soils, and water. Disposal of solid wastes in both terrestrial and oceanic environments is considered. Atmospheric transport is considered for emissions from incineration of solid wastes and for wind resuspension of particulates from surface waste deposits. Solid wastes deposited in terrestrial environments are subject to leaching by surface and ground waters. Leachates may then be transported to other surface waters and drinking water aquifers through hydrologic transport. Leachates also interact with natural organic matter, clays, and microorganisms in soils and sediments. These interactions may render chemical constituents in leachates more or less mobile, possibly change chemical and physical forms, and alter their biological activity. Oceanic waste disposal practices result in migration through diffusion and ocean currents. Surface area-to-volume ratios play a major role in the initial distributions of chemicals in the aquatic environment. Sediments serve as major sources and sinks of chemical contaminants. Food chain transport in both aquatic and terrestrial environments results in the movement of hazardous chemicals from lower to higher positions in the food web. Bioconcentration is observed in both terrestrial and aquatic food chains with certain elements and synthetic organics. Bioconcentration factors tend to be higher for synthetic organics, and higher in aquatic than in terrestrial systems. Biodilution is not atypical in terrestrial environments. Synergistic and antagonistic actions are common occurrences among chemical contaminants and can be particularly important toxicity considerations in aquatic environments receiving runoff from several terrestrial sources.